The efficiency of action of futsal goalkeepers in game situations with varying results of competition - Andrzej Szwarc; Mateusz Oszmaniec (IP Iermakov S.S., 2021)
Background and Study Aim. The aim of the study was to expand knowledge of the efficiency of actions from top-level futsal teams. Goalkeepers' activity, effectiveness and reliability were estimated with a view to implementing the objectives of the game in offence and defence and depending on the changing match status. Material and Methods. Data about the game were registered on a self-developed observation sheet. 23 goalkeepers participating in 31 matches of the World and the European Championships and the UEFA Futsal Cup played in the years 2012-2015 were observed. Results. It was found that actions to gain the playfield with the ball and to prevent a loss of a goal dominated in futsal goalkeepers' both when drawing as well as winning and losing game and that game status does not determine the style of play of the goalkeeper. Only in nine of the 60 types of actions examined significant differences in activity were fund. Conclusions. The unequivocal claim that the current score during the competition determines the style of the futsal goalkeeper's game (the frequency of taking actions in the game characteristic of his position), is unauthorized at this stage of research. The obtained significant differences in his activity in nine types of actions constitute only a small percentage (15%) of all his skills in the game. .